2020
DOI: 10.1108/prt-10-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

High performance thermoplastic polymer for the compressive behaviour of carbon fibre reinforced composites

Abstract: Purpose This paper aims to study the effect of elevated temperature on the compression behaviour of carbon fibre polyphenylene sulphide (CF/PPS) laminates notched and unnotched specimens made by film stacking method (FSM). Design/methodology/approach The surface of CF was coated with a silane coupling agent to form an effective transition layer with PPS, so as to enhance the interfacial interaction between CF and PPS. Considering the influence of fabrication pressure, forming temperature and cooling rate on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Such properties are extremely interesting for a large field of applications for high-end machinery manufacturing, nuclear engineering, aerospace, automotive industry, and orthopedic implants. [2][3][4][5][6] The research of PEEK-based biological composites has attracted extensive attention, since the biocompatibility of † These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…Such properties are extremely interesting for a large field of applications for high-end machinery manufacturing, nuclear engineering, aerospace, automotive industry, and orthopedic implants. [2][3][4][5][6] The research of PEEK-based biological composites has attracted extensive attention, since the biocompatibility of † These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…When these studies are examined, it is understood that the dominant failure modes occurring in composites exposed to impact testing are delamination, matrix cracking and fiber breakage. 5961…”
Section: Resultsmentioning
confidence: 99%
“…Thermoplastic composites are significantly sensitive to temperature. The matrix softening results in a decrease in the modulus and strength of composites, especially above the glass-transition temperature [ 28 , 29 , 30 ]. Schoßig et al found that the dynamic tensile strength and modulus of thermoplastic composites decreased with the increase in temperature [ 31 ].…”
Section: Introductionmentioning
confidence: 99%